COVID-19 vaccination efficacy in numbers including SARS-CoV-2 variants and age comparison: a meta-analysis of randomized clinical trials - Marharyta Sobczak; Rafał Pawliczak (BMC, 2022)
Abstract Background New vaccines are being developed to fight the ongoing COVID-19 pandemic. In our study we compared the efficacy of COVID-19 vaccines to prevent COVID-19-related infections and mortality. Methods 17 randomized clinical trials of COVID-19 vaccines were included after search in databases. We compared COVID-19 vaccines based on symptomatic and severe infections, number of deaths and hospitalizations related to COVID-19. Also, we analyzed the efficacy of COVID-19 against different variants of SARS-CoV-2 as well as according to different age groups. Random effects model using Mantel-Haenzeal method was used to pool relative risk (RR). Results Our meta-analysis shows that full vaccination could decrease not only the risk of symptomatic or severe COVID-19, the risk of hospitalization and death caused by COVID-19. COVID-19 vaccines were also effective against variants of SARS-CoV-2 (RR = 0.36; 95% CI [0.25; 0.53], p < 0.0001). However, efficacy of vaccination varied in COVID-19 variant-dependent manner. Moreover, the analysis in different age groups showed that COVID-19 vaccines had the similar results: the risk was slightly lower in adults compared to elderly cohort $$(\ge$$ ( ≥ 65 years): (RR = 0.16, 95% CI [0.11; 0.23]) and (RR = 0.19, 95% CI [0.12; 0.30]), respectively. Conclusions Data obtained from clinical trials of COVID-19 vaccines looks promising, in order to fully investigate efficacy of the vaccines further clinical examination is required especially considering new SARS-CoV-2 variants.